Efficiency, effectiveness and treatment stability of clear aligners: A systematic review and meta‐analysis. (26th May 2017) - Zheng, M.; Liu, R.; Ni, Z.; Yu, Z.
Structured Abstract: Objectives: The objective of this study was to perform a systematic review of the orthodontic literature with regard to efficiency, effectiveness and stability of treatment outcome with clear aligners compared with treatment with conventional brackets. Methods: An electronic search without time or language restrictions was undertaken in October 2014 in the following electronic databases: Google Scholar, the Cochrane Oral Health Group's Trials Register, Scopus, CENTRAL, MEDLINE via OVID, EMBASE via OVID and Web of Science. We also searched the reference lists of relevant articles. Quality assessment of the included articles was performed. Two authors were responsible for study selection, validity assessment and data extraction. Results: Four controlled clinical trials including a total of 252 participants satisfied the inclusion criteria. We grouped the trials into four main comparisons. One randomized controlled trial was classified as level 1B evidence, and three cohort studies were classified as level 2B evidence. Clear aligners appear to have a significant advantage with regard to chair time and treatment duration in mild‐to‐moderate cases based on several cross‐sectional studies. No other differences in stability and occlusal characteristics after treatment were found between the two systems. Conclusions: Despite claims about the effectiveness of clear aligners, evidence is generally lacking. Shortened treatment duration and chair time in mild‐to‐moderate cases appear to be the only significant effectiveness of clear aligners over conventional systems that are supported by the current evidence.